A Complex Pediatric Case: Cerebral Palsy Complicated by Severe Pneumonia and Atelectasis - Gatiningrum, Anindita; Udin, Muchammad Fahrul (Jurnal Kedokteran Brawijaya, 2025)
Cerebral palsy (CP) is a non-progressive motor and cognitive disorder resulting from brain injury during development. Cerebral palsy (CP) promotes the development of respiratory disorders, including pneumonia and atelectasis. In this case, an 8-year-old male with cerebral palsy presented with complaints of shortness of breath, intermittent fever, productive cough, and decreased appetite. His respiratory rate was 28 beats per minute, SpO2 was 85%, and temperature was 37°C. Chest X-ray showed right pleural effusion with atelectasis, pneumonia in the left lung, emphysematous lung, and thoracic scoliosis. Bronchoscopy examination showed total atelectasis in the middle lobe of the right lung, with Streptococcus mitis or Streptococcus oralis identified through microbiological examination. Individuals with CP are susceptible to respiratory diseases due to neuromuscular impairment of the laryngeal muscles. This impairment can progress to atelectasis and pneumonia, representing the most common respiratory complications in CP.